Design a system that reduces artificial lighting usage over sunlight in vertical indoor farms - Muhammad Afiq Nahar (Nanyang Technological University, 2020)
With the increase in population and the limited amount of land for organic agriculture, Singapore is aiming to advance into the vertical farming sector to increase the demand of food supply for self-sustainability by utilizing the rooftops of high-rise buildings. While major urban farming companies are leading the nation’s farming sector, some citizens are starting their own miniature farms in their own home to cultivate their produce personally. However, these gardens require space and sunlight. Unfortunately, some households do not have the perfect conditions for gardening. This report will show the research on current vertical farming methods and the light requirements of plants for optimum growth. A new design of a miniature garden that is compact and modular will be presented in the report. The personal farm prioritises natural sunlight and reduces the usage of artificial lighting for the plant to grow will be presented in the report. The model uses a lux sensor and a microcontroller to program the system. With the model, a prototype was done to ensure that the model functions as intended. The report will be concluded with the challenges faced during the project and the future developments of the product.